2016
DOI: 10.1016/j.bpj.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Shape Transformation of the Nuclear Envelope during Closed Mitosis

Abstract: The nuclear envelope (NE) in lower eukaryotes such as Schizosaccharomyces pombe undergoes large morphology changes during closed mitosis. However, which physical parameters are important in governing the shape evolution of the NE, and how defects in the dividing chromosomes/microtubules are reflected in those parameters, are fundamental questions that remain unresolved. In this study, we show that improper separation of chromosomes in genetically deficient cells leads to membrane tethering or asymmetric divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…It has been widely observed that local mechanical stimulation alters the shape and size of nuclei (Gupta et al, 2012;Ihalainen et al, 2015;Philip and Dahl, 2008;Zhu et al, 2016). Previous studies have emphasized the role of cytoskeletal distortion, with external forces transmitting the mechanical stress directly to the nuclear envelope (Balikov et al, 2017;Gupta et al, 2012;Li et al, 2014b;Lu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely observed that local mechanical stimulation alters the shape and size of nuclei (Gupta et al, 2012;Ihalainen et al, 2015;Philip and Dahl, 2008;Zhu et al, 2016). Previous studies have emphasized the role of cytoskeletal distortion, with external forces transmitting the mechanical stress directly to the nuclear envelope (Balikov et al, 2017;Gupta et al, 2012;Li et al, 2014b;Lu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…After the pioneering works by Canham [ 105 ] and Helfrich [ 106 ], the approach of energy minimization has been widely adopted in describing the shape change of biological membranes or fluid vesicles including the NE [ 107 , 108 , 109 , 110 , 111 , 112 ]. Essentially, the stable shape of NE under loading is the one that minimizes the total energy of the system.…”
Section: Continuum Models For Describing Nuclear Morphologymentioning
confidence: 99%
“…The second term of the integrand represents stretching energy density in which the membrane tension can be expressed as , with , , being areal expansion modulus, real and un-stretched membrane area, respectively. Sometimes, is treated as a constant (i.e., independent of membrane area ) because the ONM is continuous with the endoplasmic reticulum (ER) which works like a lipid reservoir to maintain the membrane tension level [ 107 , 108 , 109 ].…”
Section: Continuum Models For Describing Nuclear Morphologymentioning
confidence: 99%
“…To allow correct resolution of chromosomes in the membrane‐delimited nuclear compartment, the closed mitosis in S. pombe is associated with pronounced changes in nuclear morphology. The initial sphere‐shaped nuclear body transforms into a spherocylinder and further elongates, forming a so‐called “dumbbell structure,” which is ultimately resolved into a pair of sphere‐shaped daughter nuclei (Castagnetti, Božič, & Svetina, ; Yam et al, ; Zhu et al, ). In S. pombe , the whole process of morphological transformations and subsequent resolution of a mitotic nucleus into two daughter nuclei occurs in less than 5 min and is accompanied by a marked increase in the NE surface area (Takemoto et al, ; Yam et al, ).…”
Section: Nuclear Expansion Is Critical To Prevent Cutmentioning
confidence: 99%